Способ ручной дуговой сварки модулированным током - Князьков А. Ф. Анатолий Фёдорович; Мазель А. Г.; Дедюх Р. И. Ростислав Иванович; Азаров Н. А. Николай Антонович; Киселев А. С. Алексей Сергеевич
опубл. 15.02.82